Rape as 'one person's word against another's': challenging the conventional wisdom - Saunders, Candida L. (SAGE Publications, 2018)
According to the conventional wisdom, rape is generally a case of ‘one person’s word against another’s’ and, in the absence of independent evidence, judgements regarding the truth or otherwise of an allegation are influenced by ‘rape myths’ and gender stereotypes. The meaning of ‘one person’s word against another’s’, however, and the extent to which it accurately describes the evidence in most rape cases, or usefully explains case disposal, are largely unexplored. This article subjects the conventional wisdom of rape as ‘one person’s word against another’s’, and the implicit claims and assumptions underpinning it, to close critical scrutiny. Drawing on original empirical data, I argue that the concept of ‘one person’s word against another’s’ is vague, ambiguous, and uninformative. It tells us virtually nothing about what rape cases look like evidentially, still less about case progression, and presents a partial and misleading view of English criminal proceedings and the process of proof. If we are to better understand attrition in rape cases, we need to meaningfully engage with the contentious issue of witness credibility and reliability—not only in the absence of independent evidence that supports or corroborates a witness’s account, but in the presence of evidence that undermines or contradicts it.